Intervenções cirúrgicas para o tratamento do pectus excavatum: revisão sistemática - Silva, Marcos Vinícius Muriano da [UNESP] (2015)
Background: pectus excavatum is characterized by a depression of the anterior chest wall (sternum and lower costal cartilages) and is the most frequently occurring chest wall deformity. The prevalence ranges from 6.28 to 12 cases per 1000 around the world. Generally pectus excavatum is present at birth or is identified after a few weeks or months; however, sometimes it becomes evident only at puberty. The consequence of the condition on a individual's life is variable, some live a normal life and others have physical and psychological symptoms such as: precordial pain after exercises; impairments of pulmonary and cardiac function; shyness and social isolation. For many years, sub-perichondrial resection of the costal cartilages, with or without transverse cuneiform osteotomy of the sternum and placement of a substernal support, called conventional surgery, was the most accepted option for surgical repair of these patients. From 1980's a new surgical repair called, minimally invasive surgery, became available. This less invasive surgical option consists of the retrosternal placement of a curved metal bar, without resections of the costal cartilages or sternum osteotomy, and is performed by videothoracoscopy. However, many aspects that relate to the benefits and harms of both techniques have not been defined. Objective :To evaluate the effectiveness and safety of the conventional surgery compared with minimally invasive surgery for treating people with pectus excavatum. Method: With the aim of increasing the sensitivity of the search strategy we used only terms related to the individual's condition (pectus excavatum); terms related to the interventions, outcomes and types of studies were not included. We searched the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Embase, LILACS, and ICTPR. We considered randomized or quasi-randomized controlled trials that compared traditional surgery with minimally invasive surgery...